2020
DOI: 10.1029/2020gl090037
|View full text |Cite
|
Sign up to set email alerts
|

Observed Impacts of COVID‐19 on Urban CO2 Emissions

Abstract: • Observe a 28% decrease in urban CO 2 emissions from the San Francisco Bay Area in response to COVID-19 mobility restrictions • Changes are primarily driven by a decrease in CO 2 emissions from traffic (-44%) • Large change to the weekly and diurnal cycle of emissions with reductions in morning rush-hour emissions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 20 publications
4
67
0
Order By: Relevance
“…Bottom-up estimates using sector activity have estimated global CO 2 emissions reductions of 8.8% during the first 5 months of 2020 (Liu et al, 2020) and annual reductions from 4% to 7% (Le Quéré et al, 2020). Top-down assessments have found some indications of a decrease in CO 2 growth rate during 2020 (Buchwitz et al, 2020), with examples of substantial local and regional CO 2 and methane (CH 4 ) emissions reductions inferred from surface observations (Tohjima et al, 2020;Turner et al, 2020). However, existing satellite products could not provide the required coverage to reliably detect changes in CO 2 column densities at the magnitude expected to be occurring in 2020 (Buchwitz et al, 2020;Chevallier et al, 2020).…”
Section: Impact Of Covid-19 Lockdown On Emissionsmentioning
confidence: 99%
“…Bottom-up estimates using sector activity have estimated global CO 2 emissions reductions of 8.8% during the first 5 months of 2020 (Liu et al, 2020) and annual reductions from 4% to 7% (Le Quéré et al, 2020). Top-down assessments have found some indications of a decrease in CO 2 growth rate during 2020 (Buchwitz et al, 2020), with examples of substantial local and regional CO 2 and methane (CH 4 ) emissions reductions inferred from surface observations (Tohjima et al, 2020;Turner et al, 2020). However, existing satellite products could not provide the required coverage to reliably detect changes in CO 2 column densities at the magnitude expected to be occurring in 2020 (Buchwitz et al, 2020;Chevallier et al, 2020).…”
Section: Impact Of Covid-19 Lockdown On Emissionsmentioning
confidence: 99%
“…Although the comparison of the five stages in the first quarter of 2020, and the month-to-month comparison between 2020 and 2019 show an apparent influence of COVID-19 measures, these results include both natural carbon cycle variability and meteorological conditions. Quantifying and attributing changes in CO 2 concentrations requires accounting for meteorological effects in addition to direct emissions ( Turner et al, 2020 ). We did this by determining the difference between CO 2 excess-est and CO 2 excess-obs , as explained next.…”
Section: Resultsmentioning
confidence: 99%
“… Liu et al (2020b) reported decreases in on-road CO 2 concentrations in Beijing during COVID-19 with six on-road observations using mobile platforms. Turner et al (2020) observed a 5-50 ppm decrease in midweek CO 2 concentrations during rush hour monitoring in the San Francisco Bay Area. However, the response of averaged atmospheric CO 2 concentration to the lockdown on an urban scale is still unknown ( Pigliautile et al, 2020 ).…”
Section: Introductionmentioning
confidence: 90%
“…For example, cities in China saw reductions in NO X emissions by 20%–50% during shutdown periods ( Ding et al , 2020 ). Similarly, CO 2 emissions in the San Francisco Bay Area decreased by roughly 30% following shelter-in-place orders ( Turner et al , 2020 ). Ambient seismic noise in the 4–14 Hz range lessened globally, with the most intense effects in populous areas ( Lecocq et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%